The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/978-3-319-95693-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-Mesenchymal Transition (EMT) and Prostate Cancer

Abstract: Typically the normal epithelial cells are a single layer, held tightly by adherent proteins that prevent the mobilization of the cells from the monolayer sheet. During prostate cancer progression, the epithelial cells can undergo epithelial-mesenchymal transition or EMT, characterized by morphological changes in their phenotype from cuboidal to spindle-shaped. This is associated with biochemical changes in which epithelial cell markers such as E-cadherin and occludins are down-regulated, which leads to loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 41 publications
3
95
0
Order By: Relevance
“…EMT is characterized by switch E-cadherin to N-cadherin and Snail, thus greatly affecting the tumor metastasis [32,33,34]. As expected, we found that the knockdown of KIFC1 increased the expression of an E-cadherin, inhibited expression levels of EMT-related transcription factors N-cadherin, Snail and ZEB1, suggesting that KIFC1 is involved in the metastasis of PTC.…”
Section: Discussionsupporting
confidence: 84%
“…EMT is characterized by switch E-cadherin to N-cadherin and Snail, thus greatly affecting the tumor metastasis [32,33,34]. As expected, we found that the knockdown of KIFC1 increased the expression of an E-cadherin, inhibited expression levels of EMT-related transcription factors N-cadherin, Snail and ZEB1, suggesting that KIFC1 is involved in the metastasis of PTC.…”
Section: Discussionsupporting
confidence: 84%
“…21 During PC progression, epithelial cells undergo the EMT, characterized by morphological changes in their phenotype from cuboidal to spindle-shaped. 22 Epithelial cells predominantly express E-cadherin, whereas N-cadherin is a mesenchymal protein. Vimentin, a cytoskeleton protein, has been linked to initiation of the EMT.…”
Section: Discussionmentioning
confidence: 99%
“…The role of TGF-β in prostate tumors is a broad topic that has been extensively earlier reviewed [227][228][229][230], thus here we only provide a short outline of the mechanism of TGF-β actions in prostatic cancer cells.…”
Section: Prostate Cancermentioning
confidence: 99%